Distributed Scheme To Authenticate Data Storage Security In Cloud Computing - Bandarupalli, Rakesh; Rajitha, O.; Parveen Sultana, H. (Institute of Advanced Engineering and Science, 2018)
Cloud Computing is the revolution in current generation IT enterprise. Cloud computing displaces database and application software to the large data centers, where the management of services and data may not be predictable, where as the conventional solutions, for IT services are under proper logical, physical and personal controls. This aspect attribute, however comprises different security challenges which have not been well understood. It concentrates on cloud data storage security which has always been an important aspect of quality of service (QOS). In this paper, we designed and simulated an adaptable and efficient scheme to guarantee the correctness of user data stored in the cloud and also with some prominent features.Â Homomorphic token is used for distributed verification of erasure â coded data. By using this scheme, we can identify misbehaving servers.Â In spite of past works, our scheme supports effective and secure dynamic operations on data blocks such as data insertion, deletion and modification. In contrast to traditional solutions, where the IT services are under proper physical, logical and personnel controls, cloud computing moves the application software and databases to the large data centers, where the data management and services may not be absolutely truthful.Â This effective security and performance analysis describes that the proposed scheme is extremely flexible against malicious data modification, convoluted failures and server clouding attacks.